Comprehensive Characteristics of High-Performance Concrete with Nickel Slag as Fine and Coarse Aggregate - Lisa Oksri Nelfia; Ananda Bima Nurul Haq; Ananto Nugroho; Astri Rinanti; Bambang Endro Yuwono; Deprizon Syamsunur; Yohans Sunarno; Ouali Amiri (International Journal of Technology)
This study aimed to determine the effect of using nickel slag as an alternative aggregate for high-performance concrete. To achieve the aim, nickel slag aggregate with particle sizes of 0/5 mm and 10/20 mm was considered, using X-ray Diffraction (XRD) to analyze the compounds and minerals contained in the slag content. The investigation incorporated up to 20% Ground Granulated Blast-furnace Slag (GGBFS) as a cement substitute, while systematically replacing natural aggregate with nickel slag at a varying proportions of 0%, 20%, 40%, 60%, 80%, and 100%. The experimental result showed that Mix 2 combination achieved the highest compressive strength of 69.43 MPa. This outcome exceeded the reference concrete by 11.56% and fulfilled the classification of high-performance concrete. Additionally, XRD testing of Mix 2 samples identified the dominant compounds as C6H6O2, (Fe, Mg)SiO3, and SiO2. The results signified the promising potential of using nickel slag aggregate in concrete production, suggesting significant economic benefit for the construction industry. The outcome of this study could contribute to the growth of construction industry and reassure stakeholders about the financial viability of the project. Finally, this potential for high-performance concrete using nickel slag aggregate would create more opportunities for the future of construction industry.